Preparedness and Response to a Rural Mass Casualty Incident: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Problems contacting emergency services and delayed assistance are not unusual when incidents occur in rural areas, and the consequences can be devastating, particularly with mass casualty incidents. The IOM's Forum on Medical and Public Health Preparedness for Catastrophic Events held a workshop to examine the current capabilities of emergency response systems and the future opportunities to improve mass casualty response in rural communities.
Keywords: Health and Medicine

Preparing for the Future of Disaster Health Volunteerism: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On April 26, 2017, the Forum on Medical and Public Health Preparedness for Disasters and Emergencies convened a workshop during a 4-hour session of the 2017 Preparedness Summit. Participants discussed potential characteristics of society in the year 2042 and the key resources, tools, and opportunities necessary to support the development of a robust, scalable, and regularly engaged disaster health volunteer workforce prepared for such a future. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Increasing National Resilience to Hazards and Disasters: The Perspective from the Gulf Coast of Louisiana and Mississippi: Summary of a Workshop - Olson, Steve (The National Academies Press, 2011)
Natural disasters are having an increasing effect on the lives of people in the United States and throughout the world. Every decade, property damage caused by natural disasters and hazards doubles or triples in the United States. More than half of the U.S. population lives within 50 miles of a coast, and all Americans are at risk from such hazards as fires, earthquakes, floods, and wind. The year 2010 saw 950 natural catastrophes around the world—the second highest annual total ever—with overall losses estimated at $130 billion. The increasing impact of natural disasters and hazards points to increasing importance of resilience, the ability to prepare and plan for, absorb, recover from, or more successfully adapt to actual or potential adverse events, at the individual , local, state, national, and global levels. Assessing National Resilience to Hazards and Disasters reviews the effects of Hurricane Katrina and other natural and human-induced disasters on the Gulf Coast of Louisiana and Mississippi and to learn more about the resilience of those areas to future disasters. Topics explored in the workshop range from insurance, building codes, and critical infrastructure to private-sector issues, public health, nongovernmental organizations and governance. This workshop summary provides a rich foundation of information to help increase the nation's resilience through actionable recommendations and guidance on the best approaches to reduce adverse impacts from hazards and disasters.
Keywords: Earth Sciences

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine (The National Academies Press, 2015)
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a "return to normal." But for many American communities, pre-disaster conditions are far from optimal. Large segments of the U.S. population suffer from preventable health problems, experience inequitable access to services, and rely on overburdened health systems. A return to pre-event conditions in such cases may be short-sighted given the high costs - both economic and social - of poor health. Instead, it is important to understand that the disaster recovery process offers a series of unique and valuable opportunities to improve on the status quo. Capitalizing on these opportunities can advance the long-term health, resilience, and sustainability of communities - thereby better preparing them for future challenges. Healthy, Resilient, and Sustainable Communities After Disasters identifies and recommends recovery practices and novel programs most likely to impact overall community public health and contribute to resiliency for future incidents. This book makes the case that disaster recovery should be guided by a healthy community vision, where health considerations are integrated into all aspects of recovery planning before and after a disaster, and funding streams are leveraged in a coordinated manner and applied to health improvement priorities in order to meet human recovery needs and create healthy built and natural environments. The conceptual framework presented in Healthy, Resilient, and Sustainable Communities After Disasters lays the groundwork to achieve this goal and provides operational guidance for multiple sectors involved in community planning and disaster recovery. Healthy, Resilient, and Sustainable Communities After Disasters calls for actions at multiple levels to facilitate recovery strategies that optimize community health. With a shared healthy community vision, strategic planning that prioritizes health, and coordinated implementation, disaster recovery can result in a communities that are healthier, more livable places for current and future generations to grow and thrive - communities that are better prepared for future adversities.
Keywords: Health and Medicine; Conflict and Security Issues

Crisis Standards of Care: A Systems Framework for Catastrophic Disaster Response: Volume 1: Introduction and CSC Framework - Institute of Medicine (The National Academies Press, 2012)
Catastrophic disasters occurring in 2011 in the United States and worldwide—from the tornado in Joplin, Missouri, to the earthquake and tsunami in Japan, to the earthquake in New Zealand—have demonstrated that even prepared communities can be overwhelmed. In 2009, at the height of the influenza A (H1N1) pandemic, the Assistant Secretary for Preparedness and Response at the Department of Health and Human Services, along with the Department of Veterans Affairs and the National Highway Traffic Safety Administration, asked the Institute of Medicine (IOM) to convene a committee of experts to develop national guidance for use by state and local public health officials and health-sector agencies and institutions in establishing and implementing standards of care that should apply in disaster situations-both naturally occurring and man-made-under conditions of scarce resources. Building on the work of phase one (which is described in IOM's 2009 letter report, Guidance for Establishing Crisis Standards of Care for Use in Disaster Situations), the committee developed detailed templates enumerating the functions and tasks of the key stakeholder groups involved in crisis standards of care (CSC) planning, implementation, and public engagement-state and local governments, emergency medical services (EMS), hospitals and acute care facilities, and out-of-hospital and alternate care systems. Crisis Standards of Care provides a framework for a systems approach to the development and implementation of CSC plans, and addresses the legal issues and the ethical, palliative care, and mental health issues that agencies and organizations at each level of a disaster response should address. Please note: this report is not intended to be a detailed guide to emergency preparedness or disaster response. What is described in this report is an extrapolation of existing incident management practices and principles. Crisis Standards of Care is a seven-volume set: Volume 1 provides an overview; Volume 2 pertains to state and local governments; Volume 3 pertains to emergency medical services; Volume 4 pertains to hospitals and acute care facilities; Volume 5 pertains to out-of-hospital care and alternate care systems; Volume 6 contains a public engagement toolkit; and Volume 7 contains appendixes with additional resources.
Keywords: Health and Medicine; Conflict and Security Issues

Facing the Unexpected: Disaster Preparedness and Response in the United States - Tierney, Kathleen J.; Lindell, Michael K.; Perry, Ronald W. (The National Academies Press, 2001)
Facing the Unexpected presents the wealth of information derived from disasters around the world over the past 25 years. The authors explore how these findings can improve disaster programs, identify remaining research needs, and discuss disaster within the broader context of sustainable development.
Keywords: Explore Science; Conflict and Security Issues

Crisis Standards of Care: A Toolkit for Indicators and Triggers - Institute of Medicine (The National Academies Press, 2013)
Disasters and public health emergencies can stress health care systems to the breaking point and disrupt delivery of vital medical services. During such crises, hospitals and long-term care facilities may be without power; trained staff, ambulances, medical supplies and beds could be in short supply; and alternate care facilities may need to be used. Planning for these situations is necessary to provide the best possible health care during a crisis and, if needed, equitably allocate scarce resources. Crisis Standards of Care: A Toolkit for Indicators and Triggers examines indicators and triggers that guide the implementation of crisis standards of care and provides a discussion toolkit to help stakeholders establish indicators and triggers for their own communities. Together, indicators and triggers help guide operational decision making about providing care during public health and medical emergencies and disasters. Indicators and triggers represent the information and actions taken at specific thresholds that guide incident recognition, response, and recovery. This report discusses indicators and triggers for both a slow onset scenario, such as pandemic influenza, and a no-notice scenario, such as an earthquake. Crisis Standards of Care features discussion toolkits customized to help various stakeholders develop indicators and triggers for their own organizations, agencies, and jurisdictions. The toolkit contains scenarios, key questions, and examples of indicators, triggers, and tactics to help promote discussion. In addition to common elements designed to facilitate integrated planning, the toolkit contains chapters specifically customized for emergency management, public health, emergency medical services, hospital and acute care, and out-of-hospital care.
Keywords: Health and Medicine

Emergency Alert and Warning Systems: Current Knowledge and Future Research Directions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Following a series of natural disasters, including Hurricane Katrina, that revealed shortcomings in the nation's ability to effectively alert populations at risk, Congress passed the Warning, Alert, and Response Network (WARN) Act in 2006. Today, new technologies such as smart phones and social media platforms offer new ways to communicate with the public, and the information ecosystem is much broader, including additional official channels, such as government social media accounts, opt-in short message service (SMS)-based alerting systems, and reverse 911 systems; less official channels, such as main stream media outlets and weather applications on connected devices; and unofficial channels, such as first person reports via social media. Traditional media have also taken advantage of these new tools, including their own mobile applications to extend their reach of beyond broadcast radio, television, and cable. Furthermore, private companies have begun to take advantage of the large amounts of data about users they possess to detect events and provide alerts and warnings and other hazard-related information to their users. More than 60 years of research on the public response to alerts and warnings has yielded many insights about how people respond to information that they are at risk and the circumstances under which they are most likely to take appropriate protective action. Some, but not all, of these results have been used to inform the design and operation of alert and warning systems, and new insights continue to emerge. Emergency Alert and Warning Systems reviews the results of past research, considers new possibilities for realizing more effective alert and warning systems, explores how a more effective national alert and warning system might be created and some of the gaps in our present knowledge, and sets forth a research agenda to advance the nation's alert and warning capabilities.
Keywords: Earth Sciences; Conflict and Security Issues

Facing Hazards and Disasters: Understanding Human Dimensions - National Research Council (The National Academies Press, 2006)
Social science research conducted since the late 1970's has contributed greatly to society's ability to mitigate and adapt to natural, technological, and willful disasters. However, as evidenced by Hurricane Katrina, the Indian Ocean tsunami, the September 11, 2001 terrorist attacks on the United States, and other recent events, hazards and disaster research and its application could be improved greatly. In particular, more studies should be pursued that compare how the characteristics of different types of events—including predictability, forewarning, magnitude, and duration of impact—affect societal vulnerability and response. This book includes more than thirty recommendations for the hazards and disaster community.
Keywords: Behavioral and Social Sciences; Earth Sciences; Conflict and Security Issues

Public Response to Alerts and Warnings Using Social Media: Report of a Workshop on Current Knowledge and Research Gaps - National Research Council (The National Academies Press, 2013)
Following an earlier NRC workshop on public response to alerts and warnings delivered to mobile devices, a related workshop was held on February 28 and 29, 2012 to look at the role of social media in disaster response. This was one of the first workshops convened to look systematically at the use of social media for alerts and warnings—an event that brought together social science researchers, technologists, emergency management professionals, and other experts on how the public and emergency managers use social media in disasters.In addition to exploring how officials monitor social media, as well as the resulting privacy considerations, the workshop focused on such topics as: what is known about how the public responds to alerts and warnings; the implications of what is known about such public responses for the use of social media to provide alerts and warnings to the public; and approaches to enhancing the situational awareness of emergency managers. Public Response to Alerts and Warnings Using Social Media: Report of a Workshop on Current Knowledge and Research Gaps summarizes presentations made by invited speakers, other remarks by workshop participants, and discussions during parallel breakout sessions. It also points to potential topics for future research, as well as possible areas for future research investment, and it describes some of the challenges facing disaster managers who are seeking to incorporate social media into regular practice.
Keywords: Conflict and Security Issues; Computers and Information Technology

Exploring Disaster Risk Reduction Through Community-Level Approaches to Promote Healthy Outcomes: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On April 21, 2016, the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine convened a workshop during the 2016 Preparedness Summit, a national conference on public health preparedness. Participants discussed the concepts of disaster risk reduction, their application within U.S. communities through novel and contemporary practices, and specific strategies that can be implemented at the local level through cross-sector collaboration.
Keywords: Health and Medicine

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.
Keywords: Health and Medicine; Conflict and Security Issues

Disasters by Design: A Reassessment of Natural Hazards in the United States - Mileti, Dennis (The National Academies Press, 1999)
Disasters by Design provides an alternative and sustainable way to view, study, and manage hazards in the United States that would result in disaster-resilient communities, higher environmental quality, inter- and intragenerational equity, economic sustainability, and improved quality of life. This volume provides an overview of what is known about natural hazards, disasters, recovery, and mitigation, how research findings have been translated into policies and programs; and a sustainable hazard mitigation research agenda. Also provided is an examination of past disaster losses and hazards management over the past 20 years, including factors—demographic, climate, social—that influence loss. This volume summarizes and sets the stage for the more detailed books in the series.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues

Public Response to Alerts and Warnings on Mobile Devices: Summary of a Workshop on Current Knowledge and Research Gaps - National Research Council (The National Academies Press, 2011)
This book presents a summary of the Workshop on Public Response to Alerts and Warnings on Mobile Devices: Current Knowledge and Research Gaps, held April 13 and 14, 2010, in Washington, D.C., under the auspices of the National Research Council's Committee on Public Response to Alerts and Warnings on Mobile Devices: Current Knowledge and Research Needs.
Keywords: Computers and Information Technology; Conflict and Security Issues

Integrating Social and Behavioral Sciences Within the Weather Enterprise - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Our ability to observe and forecast severe weather events has improved markedly over the past few decades. Forecasts of snow and ice storms, hurricanes and storm surge, extreme heat, and other severe weather events are made with greater accuracy, geographic specificity, and lead time to allow people and communities to take appropriate protective measures. Yet hazardous weather continues to cause loss of life and result in other preventable social costs.
Keywords: Earth Sciences; Behavioral and Social Sciences

Geotargeted Alerts and Warnings: Report of a Workshop on Current Knowledge and Research Gaps - National Research Council (The National Academies Press, 2013)
Geotargeted Alerts and Warnings: Report of a Workshop on Current Knowledge and Research Gaps is the summary of a February, 2013 workshop convened by the Computer Science and Telecommunications Board of the National Research Council to examine precise geotargeting of public alerts and warnings using social media. The workshop brought together social science researchers, technologists, emergency management professionals, and other experts to explore what is known about how the public responds to geotargeted alerts and warnings, technologies and techniques for enhancing the geotargeting of alerts and warnings, and open research questions about how to effectively use geotargeted alerts and warnings and technology gaps. This report considers the potential for more precise geographical targeting to improve the effectiveness of disaster alerts and warnings; examines the opportunities presented by current and emerging technologies to create, deliver, and display alerts and warnings with greater geographical precision; considers the circumstances where more granular targeting would be useful; and examines the potential roles of federal, state, and local agencies and private sector information and communications providers in delivering more targeted alerts.
Keywords: Conflict and Security Issues; Computers and Information Technology

A Guide to Regional Transportation Planning for Disasters, Emergencies, and Significant Events - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 777: A Guide to Regional Transportation Planning for Disasters, Emergencies, and Significant Events uses foundational planning principles, case studies, tips, and tools to explain implementation of transportation planning for possible multijurisdictional disasters, emergencies, and other major events. In addition to the guide, there is a contractor's final research report and a PowerPoint presentation describing the entire project.
Keywords: Transportation and Infrastructure

Implications of the California Wildfires for Health, Communities, and Preparedness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
California and other wildfire-prone western states have experienced a substantial increase in the number and intensity of wildfires in recent years. Wildlands and climate experts expect these trends to continue and quite likely to worsen in coming years. Wildfires and other disasters can be particularly devastating for vulnerable communities. Members of these communities tend to experience worse health outcomes from disasters, have fewer resources for responding and rebuilding, and receive less assistance from state, local, and federal agencies. Because burning wood releases particulate matter and other toxicants, the health effects of wildfires extend well beyond burns. In addition, deposition of toxicants in soil and water can result in chronic as well as acute exposures. On June 4-5, 2019, four different entities within the National Academies of Sciences, Engineering, and Medicine held a workshop titled Implications of the California Wildfires for Health, Communities, and Preparedness at the Betty Irene Moore School of Nursing at the University of California, Davis. The workshop explored the population health, environmental health, emergency preparedness, and health equity consequences of increasingly strong and numerous wildfires, particularly in California. This publication is a summary of the presentations and discussion of the workshop.
Keywords: Health and Medicine

Strengthening Post-Hurricane Supply Chain Resilience: Observations from Hurricanes Harvey, Irma, and Maria - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Resilient supply chains are crucial to maintaining the consistent delivery of goods and services to the American people. The modern economy has made supply chains more interconnected than ever, while also expanding both their range and fragility. In the third quarter of 2017, Hurricanes Harvey, Irma and Maria revealed some significant vulnerabilities in the national and regional supply chains of Texas, Florida, the U.S. Virgin Islands, and Puerto Rico. The broad impacts and quick succession of these three hurricanes also shed light on the effectiveness of the nation's disaster logistics efforts during response through recovery. Drawing on lessons learned during the 2017 hurricanes, this report explores future strategies to improve supply chain management in disaster situations. This report makes recommendations to strengthen the roles of continuity planning, partnerships between civic leaders with small businesses, and infrastructure investment to ensure that essential supply chains will remain operational in the next major disaster. Focusing on the supply chains food, fuel, water, pharmaceutical, and medical supplies, the recommendations of this report will assist the Federal Emergency Management Agency as well as state and local officials, private sector decision makers, civic leaders, and others who can help ensure that supply chains remain robust and resilient in the face of natural disasters.
Keywords: Conflict and Security Issues; Earth Sciences

National Earthquake Resilience: Research, Implementation, and Outreach - National Research Council (The National Academies Press, 2011)
The United States will certainly be subject to damaging earthquakes in the future. Some of these earthquakes will occur in highly populated and vulnerable areas. Coping with moderate earthquakes is not a reliable indicator of preparedness for a major earthquake in a populated area. The recent, disastrous, magnitude-9 earthquake that struck northern Japan demonstrates the threat that earthquakes pose. Moreover, the cascading nature of impacts-the earthquake causing a tsunami, cutting electrical power supplies, and stopping the pumps needed to cool nuclear reactors-demonstrates the potential complexity of an earthquake disaster. Such compound disasters can strike any earthquake-prone populated area. National Earthquake Resilience presents a roadmap for increasing our national resilience to earthquakes. The National Earthquake Hazards Reduction Program (NEHRP) is the multi-agency program mandated by Congress to undertake activities to reduce the effects of future earthquakes in the United States. The National Institute of Standards and Technology (NIST)-the lead NEHRP agency-commissioned the National Research Council (NRC) to develop a roadmap for earthquake hazard and risk reduction in the United States that would be based on the goals and objectives for achieving national earthquake resilience described in the 2008 NEHRP Strategic Plan. National Earthquake Resilience does this by assessing the activities and costs that would be required for the nation to achieve earthquake resilience in 20 years. National Earthquake Resilience interprets resilience broadly to incorporate engineering/science (physical), social/economic (behavioral), and institutional (governing) dimensions. Resilience encompasses both pre-disaster preparedness activities and post-disaster response. In combination, these will enhance the robustness of communities in all earthquake-vulnerable regions of our nation so that they can function adequately following damaging earthquakes. While National Earthquake Resilience is written primarily for the NEHRP, it also speaks to a broader audience of policy makers, earth scientists, and emergency managers.
Keywords: Earth Sciences; Conflict and Security Issues